(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
Pedagogue B. Rudenko said that mnemonics is the key to this puzzle. Solving these puzzles is the task of skilled pedagogues. The article examines the search and application of effective methods of memorizing historical vocabulary based on methods of memory enhancement and personality development approaches within the framework of modern mnemonics. In particular, all the methods used in the article are valuable for their novelty. Because today, New Pedagogues of New Uzbekistan are required to conduct teaching processes using new methods.